Three-year randomized study of manual and power toothbrush effects on pre-existing gingival recession - Dörfer, Christof; Staehle, Hans Jörg; Wolff, Diana (Journal of clinical periodontology, 2016)
Aim To compare long-term effects of brushing with an oscillating-rotating power toothbrush or an ADA reference manual toothbrush on pre-existing gingival recession. Materials and Methods In this controlled, prospective, single-blind, parallel-group study, healthy subjects with pre-existing recession were randomized and brushed with a power toothbrush (n = 55) or an ADA reference manual toothbrush (n = 54) for a 3-year study period. Subjects were required to brush their teeth twice daily for 2 min. using a standard fluoride toothpaste. During the study, subjects were assessed for clinical attachment loss and probing pocket depths to the nearest mm at six sites per tooth by the same calibrated examiner. Gingival recession was calculated at pre-existing sites as the difference between clinical attachment loss and probing pocket depths. Hard and soft oral tissues were examined to assess safety. Results After 35 ± 2 months, mean gingival recession did not differ significantly between groups, but was significantly reduced from baseline (p < 0.001), from 2.35 ± 0.35 mm to 1.90 ± 0.58 mm in the power and from 2.26 ± 0.31 mm to 1.81 ± 0.66 mm in the manual group. Conclusions Gingival recession in subjects with pre-existing recession was significantly reduced after 3 years of brushing with either a power or manual toothbrush.
Gesehen am 11.05.2020